Quality of groundwater from domestic wells in the Great Bend Prairie Aquifer, Kansas, USA - Armijo, Brooklyn (Kansas State University, 2022)
The High Plains aquifer supplies nearly one-third of the irrigation water used in the U.S. and drinking water for millions of people, making it a critical groundwater resource. Recent research indicates that nitrate accumulation is degrading groundwater quality in the Great Bend Prairie Aquifer, a portion of the High Plains Aquifer in south-central Kansas. However, little is known about the extent of the problem for domestic (i.e., private) wells, which are used by >30,000 people in the area. To fill this knowledge gap, we collected and geochemically analyzed groundwater samples from 63 domestic wells in the aquifer and combined our results with data collected in 2016 from 23 monitoring wells. We characterized water quality relative to standards for drinking water and used our results in mixing and geospatial calculations to better understand sources of salinity and relationships to land use, respectively. In the private well samples, nitrate as N concentrations averaged 11.2 mg/L as N and exceeded the U.S. Environmental Protection Agency maximum contaminant level for public water supplies (10 mg/L as N) in 28 of 63 samples. Chloride, and sulfate concentrations exceeded the standards in five private water samples. We found that nitrate and uranium concentrations significantly correlate, consistent with studies that have found that nitrate contamination can trigger uranium release from sediments. Using 10 different land use/land cover classes and buffer zones of different radii around each well, we evaluated correlations between nitrate contamination and land use. Primarily, we found negative relationships between the occurrence of nitrate and the urban land use/land cover class. We used a mixing analysis to evaluate the impact on salinity from nearby oil and gas development, evapotranspiration, and natural brine contribution from geological formations underlying the aquifer. Agreeing with previous findings, our results demonstrate that the main contributor of salinity in the aquifer is Permian saltwater, although some data points show influence from evapotranspiration and contamination from oil and gas brine. We expect that these results will better define the scale of the nitrate contamination and general water quality concerns and their links to land use in the study region.
Keywords: Groundwater; Nitrate; Aquifer; Contamination